Bariatric Surgery in Hypothalamic Obesity - Bingham, Nathan; Rose, Susan; Inge, Thomas (Frontiers in Endocrinology, 2012)
Craniopharyngiomas (CP) are epithelial neoplasms generally found in the area of the pituitary and hypothalamus. Despite benign histology, these tumors and/or their treatment often result in significant, debilitating disorders of endocrine, neurological, behavioral, and metabolic systems. Severe obesity is observed in a high percentage of patients with CP resulting in significant comorbidities and negatively impacting quality of life. Obesity occurs as a result of hypothalamic damage and disruption of normal homeostatic mechanisms regulating energy balance. Such pathological weight gain, termed hypothalamic obesity (HyOb), is often severe and refractory to therapy. Unfortunately, neither lifestyle intervention nor pharmacotherapy has proven effective in the treatment of HyOb. Given the limited choices and poor results of these treatments, several groups have examined bariatric surgery as a treatment alternative for patients with CP–HyOb. While a large body of evidence exists supporting the use of bariatric surgery in the treatment of exogenous obesity and its comorbidities, its role in the treatment of HyOb has yet to be defined. To date, the existing literature on bariatric surgery in CP–HyOb is largely limited to case reports and series with short term follow-up. Here we review the current reports on the use of bariatric surgery in the treatment of CP–HyOb. We also compare these results to those reported for other populations of HyOb, including Prader–Willi Syndrome, Bardet–Biedl syndrome, and hypothalamic melanocortin signaling defects. While initial reports of bariatric surgery in CP–HyOb are promising, their limited scope makes it difficult to draw any substantial conclusions as to the long term safety and efficacy of bariatric surgery in CP–HyOb. There continues to be a need for more robust, controlled, prospective studies with long term follow-up in order to better define the role of bariatric surgery in the treatment of HyOb.